Unity Makes Strength: Exploring Intraspecies and Interspecies Toxin Synergism between Phospholipases A2 and Cytotoxins - Pucca, Manuela B.; Ahmadi, Shirin; Cerni, Felipe A.; Ledsgaard, Line; Sørensen, Christoffer V.; McGeoghan, Farrell T. S.; Stewart, Trenton; Schoof, Erwin; Lomonte, Bruno; auf dem Keller, Ulrich; Arantes, Eliane C.; Çalışkan, Figen; et al. (Frontiers in Pharmacology, 2020)
Toxin synergism is a complex biochemical phenomenon, where different animal venom proteins interact either directly or indirectly to potentiate toxicity to a level that is above the sum of the toxicities of the individual toxins. This provides the animals possessing venoms with synergistically enhanced toxicity with a metabolic advantage, since less venom is needed to inflict potent toxic effects in prey and predators. Among the toxins that are known for interacting synergistically are cytotoxins from snake venoms, phospholipases A2 from snake and bee venoms, and melittin from bee venom. These toxins may derive a synergistically enhanced toxicity via formation of toxin complexes by hetero-oligomerization. Using a human keratinocyte assay mimicking human epidermis in vitro, we demonstrate and quantify the level of synergistically enhanced toxicity for twelve cytotoxin/melittin-PLA2 combinations using toxins from elapids, vipers, and bees. Moreover, by utilizing an interaction-based assay and by conducting a thorough literature review, we speculate and propose a mechanistic model for how toxin synergism in relation to cytotoxicity may be mediated by cytotoxin/melittin and PLA2 complex formation.